Some characterizations of the properties (DN) and (Ω) - Hai, Le Mau; van Khue, Nguyen (MATHEMATICA SCANDINAVICA, 2000)
The aim of this paper is to show that 7816H_w(B,F) = H(B,F)7816 for every LB^∞-regular compact set B in a Frechet space E if and only if F is a Frechet space having property (DN). At the same time, the equivalence between the existence of the LB^∞-regular compact set B in a Schwartz-Frechet space E with an absolute basis and the property (Ω) also established here.